The Impact of Communities of Practice on Professional Development Among Chinese Teachers: A Mixed-Methods Longitudinal Study - Youjing Wang; Zhongtao Fan (SAGE Open)
This study investigates the impact of Communities of Practice (CoPs) on the professional development of Chinese teachers, focusing on collaborative learning, skill development, and job satisfaction within the unique cultural context of Chinese education. Using a mixed-methods longitudinal design, the research spanned 18 months and involved 135 in-service teachers from diverse regions across China. Qualitative data were collected through semi-structured interviews, while quantitative data were gathered through surveys administered at the beginning and end of the study. The qualitative findings highlight the complex interplay between cultural norms, collaborative processes, and teachers' professional growth within CoPs. Teachers emphasized the value of CoPs in fostering a sense of community, providing opportunities for peer learning and feedback, and supporting the development of their professional identities. While navigating cultural challenges related to hierarchy and “saving face,” teachers also underscored the importance of CoPs in promoting collaboration and knowledge sharing. The quantitative findings revealed statistically significant improvements in collaborative learning, skill development, and job satisfaction, with large effect sizes observed in collaborative learning and medium effect sizes in skill development and job satisfaction. These findings demonstrate the multifaceted ways in which CoPs can contribute to the professional growth and well-being of Chinese teachers, offering valuable insights for policymakers and school leaders seeking to promote effective and culturally responsive professional development initiatives.